Pityogenes chalcographus (Coleoptera, Scolytinae) at the southernmost borderline of Norway spruce (Picea abies) in Greece - Avtzis, D.N.; Arthofer, W.; Stauffer, C.; Avtzis, N.; Wegensteiner, R. (ENTOMOLOGIA HELLENICA, 2017)
The six toothed bark beetle, Pityogenes chalcographus L. (Coleoptera: Scolytinae) is a widely distributed pest in Europe, infesting mainly Norway spruce (Picea abies) as well as other conifer species such as Pinus sp., Abies alba, Larix deciduas, L. sibirica and Pseudotsuga douglasii. Even though the distribution of this bark beetle coincides that of its main host tree, P. abies, the occurrence of P. chalcographus has never been recorded in the spruce forest of Elatia-Drama, Northern Greece, which is the southernmost area of the natural, autochthonous distribution of P. abies. In this study we installed five pheromone traps baited with chalcogran dispensers in the forest of Elatia. The total number of bark beetles attracted to these traps exceeded several thousands of individuals. Norway spruce trees growing in the natural forest of Elatia demonstrate low vigor, something that can be attributed to the marginal environmental conditions in concert with the effects of climate change. The combination of these factors inhibits the regular growth of spruce, rendering trees more susceptible to the attack of P. chalcographus.